Clinical and epidemiological features of West Nile virus equine encephalitis in New South Wales, Australia, 2011. Issue 5 (25th April 2019) - Read, AJ; Finlaison, DS; Gu, X; Hick, PM; Moloney, BJ; Wright, T; Kirkland, PD
Abstract : Background: Between February and June 2011, more than 300 horses with unexplained neurological disease were observed in New South Wales, Australia. A virulent strain of West Nile virus (WNVNSW2011 ), of Australian origin, was shown to be the cause of many of these cases. Methods: We reviewed the clinical descriptions provided by veterinary practitioners and the associated laboratory results. Although there was a range of clinical signs described, ataxia was the only sign that was consistently described in laboratory‐confirmed cases. Results: WNV was detected in brain samples by real‐time reverse transcription PCR assay and virus isolation. For serological confirmation of clinical cases, an equine IgM ELISA specific for WNV was shown to be the most effective tool. Conclusion: A state‐wide serological survey undertaken after the outbreak indicated that, contrary to expectation, although infection had been widespread, the seroprevalence of antibodies to WNV was very low, suggesting that there could be a significant risk of future disease outbreaks.